Epigenetic Responses to Anthropogenic Versus Natural Sources of Oil Exposure Differ in Wild Arctic Seabird Populations - Wing‐Zheng Ho; Åsa Lind; Reyd Dupuis‐Smith; Frederic Dwyer‐Samuel; Samantha Pilgrim; George Gear; Rodd Laing; Gregg Tomy; Mark L. Mallory; Jamie Enook; Yasmeen Zahaby; Jennifer F. Provencher; et al. (Evolutionary Applications)
ABSTRACT Anthropogenic pollution can have detrimental effects on organismal physiology, behavior, and fitness, but the underlying genomic mechanisms mediating these effects are not well understood. Epigenetic regulation, such as DNA methylation, has been proposed as a potential mechanism mediating these effects, but currently, there are few studies in wild populations. Here, we examined the methylation patterns of liver tissues from black guillemot (Cepphus grylle) in regions of the Canadian Arctic with different histories of exposure to polycyclic aromatic compounds (PACs)—contaminants associated with hydrocarbons and petrochemicals. As compared to a reference site with minimal PAC exposure, the two sites with exposure to anthropogenic sources of PACs (shipping and spills) shared more differentially methylated regions (DMRs) than they did with the site experiencing chronic exposure to natural PACs (a hydrocarbon seep). Furthermore, we found that guillemots that have been exposed to anthropogenic PACs are characterized by having DMRs with significantly greater ratios of hypermethylated to hypomethylated DNA versus the population experiencing chronic exposure to natural PACs. However, birds from all three sites with elevated PAC exposure shared a core set of DMRs, implying that there are some consistent methylation responses to this family of compounds. Taken together, these results imply that the specific composition and exposure length of PACs can influence the direction of the epigenetic response. The identified DMRs serve as a genomic resource for further research investigating the functional role of DNA methylation in response to anthropogenic oil pollution.